Wild mint (Mentha longifolia) extracts in the production of non-alcoholic beverages - Stanisavljevic, Dragana M; Dordevic, Sofija M; Milenkovic, Marina T; Zlatkovic, Branislav P; Nikolova, Milena T; Velickovic, Dragan T (Progress in Nutrition, 2019)
Isolates of medicinal and aromatic herbs are used as additives in non-alcoholic drinks to improve the sensory characteristics and antioxidant potential. The method of drying the plant material, among other factors, has a profound influence on the chemical composition and pharmacological activities of plant extracts. This paper analyzes the effect of the drying technique (I - natural drying, II - in the laboratory oven, III - in low-temperature condensational drier) on the volatile fraction of the wild mint (Mentha longifolia (L.) Hudson) extract, in order to select an extract of the best quality for preparation of non-alcoholic drinks. The volatile profile of the extracts was determined by the GC-FID and GC-MS techniques, the antimicrobial activity by the microdilution technique, the antioxidant activity by the DPPH and FRAP assays, and the sensory acceptance according to the Regulation on quality for refreshing non-alcoholic beverages. The results showed that piperitone was the major component of the volatile fraction extract of the natural drying herb and low-temperature condensational drier herb (53.9% and 61.1%, respectively), while the extract of laboratory oven herb was rich in menthone (35.5%). At the concentrations in the range of 0.8-3.2 mg/mL the extracts better inhibited the Gram (+) bacteria. The beverage to which the extract of naturally dried wild mint was added, showed the antioxidant activity (9.09+-0.17 μmol Fe2+/mL by FRAP and 14.00+-3.00 μL/mL by DPPH method) and good sensorial characteristics (concentration of the extract 0.8 g/L).